Pendekatan Kebidanan Holistik untuk Mensejahterakan dan Relaksasi dengan Pijat pada Ibu Nifas - Zara Elfiani; Nova Yulita (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The aim of this research is to find out the effectiveness of massage techniques for postpartum mothers who experience pain after giving birth and get relaxation after massage. This research uses a case study method using qualitative descriptive methods. This research was conducted on Jl. Kapau Sari, East Tangkerang, District. Tenayan Raya, Pekanbaru city 28282, Indonesia in 2024. The target of this research is multiparous NY.M aged 30 years. Data that can be obtained and used in research is primary data and secondary data. What was obtained from the research results showed that there were benefits felt by clients after massage in terms of reducing the pain felt after giving birth.